2011
DOI: 10.1038/ijo.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin sensitivity is accompanied by disturbances in skeletal muscle fatty acid handling in subjects with impaired glucose metabolism

Abstract: Objective: To determine insulin sensitivity and skeletal muscle fatty acid (FA) handling at baseline and after a high-fat mixed meal in impaired fasting glucose (IFG), impaired glucose tolerance (IGT), IFG/IGT and normal glucose tolerance (NGT) subjects. Design: In this multi-center study, insulin sensitivity and b-cell function were assessed (n ¼ 102), using a euglycemichyperinsulinemic and hyperglycemic clamp with additional arginine stimulation and a 75 g oral glucose tolerance test. Fasting and postprandia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
1
26
1
Order By: Relevance
“…This result is in quantitative agreement with data from previous studies in insulin-resistant obese Zucker rats using orally administered 14 C-labelled lipids [20, 21]. However, in contrast to these reports and our own data, other studies have shown an increased postprandial muscle lipid uptake in insulin-resistant individuals and animals [8, 11, 15]. In addition, in vitro measurements in isolated muscle preparations and giant sarcolemmal vesicles yielded increased lipid uptake rates in muscle from insulin-resistant obese individuals and obese Zucker rats [7, 10, 13, 14].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in quantitative agreement with data from previous studies in insulin-resistant obese Zucker rats using orally administered 14 C-labelled lipids [20, 21]. However, in contrast to these reports and our own data, other studies have shown an increased postprandial muscle lipid uptake in insulin-resistant individuals and animals [8, 11, 15]. In addition, in vitro measurements in isolated muscle preparations and giant sarcolemmal vesicles yielded increased lipid uptake rates in muscle from insulin-resistant obese individuals and obese Zucker rats [7, 10, 13, 14].…”
Section: Discussionsupporting
confidence: 92%
“…A post hoc power analysis showed a potential to detect a relative difference in ISec 0-12 of 65%, with 80% power and a = 0.05. This can be compared with a relative difference of 80% in first-phase C-peptide secretion between normal glucose tolerance and IFG/IGT in a recent study (30). We were able to use a goldstandard technique for estimation of insulin secretion and insulin sensitivity (hyperglycemic clamp), which to our knowledge has not been used before in this field of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired insulin signaling, as observed in subjects with obesity and type 2 diabetes, is strongly associated with an excess accumulation of triacylglycerols (TAGs) within muscle fibers in skeletal muscle (2)(3)(4)(5). TAGs are mainly stored in neutral lipid droplets (LDs), coated by lipid droplet-associated proteins which are referred to as perilipins (6,7).…”
Section: Introductionmentioning
confidence: 99%